Determination of Lead, Cadmium, Arsenic, Iron, Zinc, Copper, Nickel and Magnesium in Some Cultivated Agaricus bisporus and Pleurotus ostreatus Mushrooms of Iran - DOWLATABADI BAZAZ, REZA; PIRALI-HAMEDANI, MORTEZA; ABDI, KHOSRO; BAYRAMI, ZAHRA; RABIEI, MARYAM; JAFARI, MOSTAFA (Asian Journal of Chemistry, 2010)
Several samples of Agaricus bisporus and Pleurotus ostreatus mushrooms from different cultivation farms were collected from the market and after sample preparation were tested by flame atomic absorption spectroscopy for measuring copper, zinc, iron and magnesium. Graphite furnace atomic absorption spectroscopy was applied for measuring cadmium, lead, nickel and arsenic. The results of this study showed that content of all measured elements were in close accordance with the similar studies performed previously in other countries.